Isoflavone content of soy dietary supplements (Revista Brasileira de Ciências Farmacêuticas, 2003)
Because of the possible health effects, a large number of soy isoflavone products are now available on the Brazilian market. Our objective was to determine the isoflavone content and distribution in soy dietary supplements commercialized in Brazil and verify the accordance to the isoflavone content supplied by the producers. Determinations were made by high performance liquid chromatography and photodiode array detection of the intact isoflavones without acid hydrolysis. Total isoflavone content varied significantly among products, from 3 to 22 mg/100 g (expressed as aglycones) and was much lower than the values found in the product labels (27 to 86% less). Isoflavone distribution varied according to isoflavone source and products could be classified in two groups, those having daidzein predominance and those having genistein predominance. Based on these data, we conclude that there is a need of better standardization and quality control of these products and also a clear regulation.